Micropropagation and acclimatization of Stevia rebaudiana Bertoni - Kittisak Chotikadachanarong (2018)
Multiple shoot induction of Stevia rebaudiana Bertoni was studied by node explants that were cultured on solidified MS media and supplemented with 0, 1, 2, 3 and 4 mg L-1 kinetin for 4 weeks. The results showed the maximum amount of multiple shoot induction (9.31±4.17 shoots/explant) when cultured on MS media supplemented with 3 mg L-1 kinetin. In vitro shoots were rooted on solidified MS media supplemented with 0, 0.1, 0.5 and 2 mg L-1 Naphthaleneacetic Acid (NAA) for 4 weeks. The highest number of roots (11.18±1.34 roots/shoot) was detected on a concentration of 0.1 mg L-1 NAA while the high survival rate (80%) was obtained when the rooted plantlets were transferred to greenhouse conditions. © 2013 Asian Network for Scientific Information.